Quality Assurance in Faith-Based Education: A Case Study of MA Muhammadiyah 1 Kota Yogyakarta - Mustaghfiroh, Risalatun; Asri, Diah Ayu Purwita; Cahyani, Rysma Nur; Mustofa, Rizal; Amalia, Khoirunnisa (Journal of Islamic Education Management Research, 2025)
Purpose – This study aims to examine the quality assurance system at MA Muhammadiyah 1 Kota Yogyakarta and to analyze how institutional policies align with graduate outcomes and stakeholder satisfaction within a faith-based secondary school context. Design/methods – This research employs a qualitative single-site case study design. Data were collected through in-depth interviews with school leaders and teachers, direct classroom and institutional observations, and document analysis of internal policies and quality assurance records. The data were analyzed using inductive thematic analysis, supported by triangulation, member checking, and audit trails to ensure trustworthiness. Findings – The findings reveal that strong religious culture, structured disciplinary systems, adaptive pedagogy, teacher professionalism, and strategic utilization of facilities contribute significantly to high graduate quality and positive stakeholder perceptions. Graduates demonstrate discipline, religious commitment, resilience, communication skills, and collaborative competence. However, challenges remain, including limited digital integration, uneven student participation in quality assurance processes, restricted technology access for boarding students, and limited dissemination of teaching innovations beyond the institution. Research implications/limitations – This study is limited by its single-case qualitative design and reliance on participant perspectives, which may restrict the generalizability of the findings. Future research should adopt comparative or mixed-method approaches across multiple madrasah to deepen understanding of quality assurance implementation in diverse faith-based educational contexts. Practical implications – The study suggests that quality assurance in Islamic secondary education should be multidimensional, integrating academic, spiritual, social, and managerial dimensions. Schools are encouraged to strengthen technology-enhanced quality assurance systems, expand student involvement in evaluation processes, and promote structured professional development and knowledge-sharing mechanisms to support continuous improvement. Originality/value – This study contributes original empirical insights into the enactment of quality assurance at the madrasah level, an area that remains underexplored in the literature. By providing a context-sensitive analysis of quality assurance in a faith-based secondary school, the study bridges policy-level discussions and everyday school practices, offering a nuanced model for improving quality assurance in Islamic education.